EKSISTENSI PERSIDANGAN ELEKTRONIK (Kajian Tematik Seputar Asas-asas Peradilan) - Hidayatullah, Muhammad Syarif; Firman Wahyudi (Institut Agama Islam Darul Ulum Kandangan, 2023)
The development of the times and the era of disruption with the influence of digitalization are so significant that digital technology has penetrated various sectors in today's modern era. One of them is the optimization of digital technology in the field of law in judicial practice. This paper aims to describe electronic trials and correlate them with the verses of the Koran regarding the principles of justice. The research method applied is normative legal research with a conceptual approach. Based on the studies conducted, the electronic trial that began to be widely practiced now has a juridical foundation, namely Perma No. 1 of 2019 concerning Case Administration and electronic trials. The procedure of the trial electronically is the same as the ordinary trial. The difference is in the media used. Meanwhile, the existence of electronic evidence in the framework of civil law is still debatable, whether it stands alone as evidence or is an extension of the meaning of written evidence. In its correlation with the qur'anic verse, it can be concluded that electronic justice containing the principles of justice, peace, avoiding access to bribes and illegal levies and providing convenience according to simple principles, fast and light costs have relevance to the values contained in the verses of the Qur'an.